Composition design and characterization of alkali-activated Slag–Metakaolin materials - Zhan, Jianghuai; Li, Hongbo; Li, Huang; Cheng, Zhenyun; Fu, Bo (Frontiers in Built Environment, 2022)
This study explores the effects of the interactions among Na2O content, metakaolin content, activator modulus on the compressive strength and autogenous shrinkage of alkali-activated slag–metakaolin (AASM) cementitious composite materials. The Box–Behnken RSM design was used to create an experimental scheme, establish a model, and optimize the mix proportions. Fourier transform infrared spectroscopy, scanning electron microscopy, and mercury intrusion experiment were used to analyze the compositions, microstructures, and pore structures of the hydration products of the AASM cementitious composite materials, respectively. Results showed that the interactions between the activator modulus and metakaolin content as well as Na2O content and metakaolin content are the key factors affecting the compressive strength and autogenous shrinkage, respectively, of the AASM cementitious composite materials. Under the optimal conditions of Na2O content of 6%, sodium silicate modulus of 1.5, and metakaolin/slag ratio of 1: 3, the relative errors in the model verification test for compressive strength and autogenous shrinkage are 0% and 0.18%, respectively. In the water glass modulus and metakaolin content interaction, Ca2+, A13+, and Si4+ ions in the composite system react with several [SiO4]4− groups to form C-A-S-H and N-A-S-H gels, which fill each other to make the composite structure denser. When Na2O interacts with metakaolin, the OH− and Na+ in the solution react with A13+ and Si4+ to generate additional N-A-S-H, thereby reducing the compressive strength of the composite system, mitigating autogenous shrinkage, and increasing volume stability.